Intersectional pedagogy : Complicating identity and social justice - Case, Kim A. (Routledge, 2017)
Intersectional Pedagogy explores best practices for effective teaching and learning about intersections of identity as informed by intersectional theory. Formatted in three easy-to-follow sections, this collection explores the pedagogy of intersectionality to address lived experiences that result from privileged and oppressed identities. After an initial overview of intersectional foundations and theory, the collection offers classroom strategies and approaches for teaching and learning about intersectionality and social justice. With contributions from scholars in education, psychology, sociology and women’s studies, Intersectional Pedagogy include a range of disciplinary perspectives and evidence-based pedagogy.
Keywords: approches et analyses; discipline; formations; féminisme décolonial; identités; intersectionnalité; justice sociale; outils; ouvrages de références; psychologie; pédagogie; ressource en ligne; sciences de l'éducation; sciences humaines; sociologie; thématiques; études de genres

Le positionnement intersectionnel comme pratique de recherche: faire avec les dynamiques de pouvoir entre femmes - Marcillat, Audrey; Miramond, Estelle; Rupert, Nouri; Çıngı Kocadost, Fatma (Les cahiers du CEDREF, 2017)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; cours; discipline; intersectionnalité; inégalités; militance; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; sexisme; soc3113; sociologie; systèmes d'oppressions; thématiques; états-unis